Scientific Research Methodologies in Advanced Quranic Studies: Challenges and Ways of Development - Al-Ryahneh, Fadi Mahmoud (Journal of Ecohumanism, 2024)
In light of the pivotal role of scientific research, world powers vie for extensive research institutions and allocate hefty budgets for them. Universities have responded by creating specialized faculties for scientific and postgraduate studies, all aimed at fostering distinguished research. These efforts seek to enhance human knowledge with innovative scientific and practical advancements and uncover new truths, a practice embraced by progressive nations to meet societal needs that evolve with time and place. Scientific research in advanced Quranic studies is integral to this trend, emerging as a critical project within the "review and development" discourse. It is an urgent necessity, driven by the era's fast-paced changes, and faces challenges that hinder its developmental potential and societal contribution. We aim for further innovation in the methodologies of scientific research in Quranic studies, calling for a coalition of efforts among scholars and researchers. Emphasizing the utilization of field studies and comprehensive research, alongside modern technologies, is paramount in advancing this field.